Communication Cues, Identities and Errors of English in the Bottom-up Linguistic Landscape in Ado-Ekiti, Nigeria - ADEDOTUN, Toyin Florence (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Communication identity in linguistic landscape is a means in which sign producers express their linguistic or cultural background in their signage. This also influences the sign consumers to form their understanding of signage emplaced. However, linguistic landscape (LL) makeup is often shaped by extra-linguistic factors such as, the background, culture and environment. As a result of dichotomy in the language use in the society, most bottom up signage are characterised by the use of the English language and do not showcase the local identity. The study examined how sign producers reflect their identity focusing on the language errors and reproduction on the selected bottom-up signage. It also explored whether these signs communicate effectively to sign-viewers/consumers. The study adopted descriptive qualitative approach using geosemiotics theory to analyse how language elements in public discourse convey meaning beyond their literal interpretation. Signage around Ado-Ekiti metropolis were used for the study. Relevant articles, journals and archives were sourced to gather information for the study. The findings of the study showed that most signage reflect errors like grammatical errors, substitution, sound deletion, substitution and reproduction of English in their use of the English language. The choice of language used on these signage is informed largely by attitudes towards the use of the English language being a Lingua Franca and assumed that it is widely used in their environment. The study concluded that most of the bottom-up signage reproduced the ideologies of the top-down signage hence, the local language is not found on the signage.